Kepastian Hukum Pelaksanaan Khiyar Syarat Dalam Bai’Salam Online Melalui Instagram - Wahyu Wahyu; Rahmadi Indra Tektona (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2020)
Islam strongly emphasizes that all economic activities carried out by humans in the world are an accountability that must be in accordance with Islamic law. In the Sharia economy there are khiyar rights which are expected to provide good benefits in the sale and purchase agreement and make buying and selling activities in accordance with the principles of Islamic law, it is consensual and also providing benefits to the parties in accordance with the provisions in Islamic law and the existence of willingness or sincerity in buying and selling activities in accordance with the Koran and hadith. Currently, many buying and selling transactions are carried out online, one of which is using the social media, Instagram, which has millions of users who can exceed time and space. Many business actors ranging from housewives, students, state employees, private employees who post goods to be traded on Instagram, behind this convenience, of course there are problems, it is the existing image and the merchant’s reputation is something that is highly valued in online trading. The problem that arises in the online buying and selling contract is the mismatch of goods with pictures and descriptions on social media resulting in a one-sided cancellation of the purchase of ordered goods by the buyer and this results in losses to the seller, even though before the transaction the two parties have mutually agreed. The research objective of this paper was to analyze legal certainty in the implementation of khiyar in purchasing ordered goods in online buying and selling transactions via Instagram, the research method used is normative juridical, the results of research on the form of legal certainty in the implementation of khiyar. Keywords: Legal certainty, Khiyar Syarat, Bai’ Salam Online